L’association entre le carcinome hépatocellulaire et le pronostic des patients cirrhotiques de la région de Mostaganem - Korichi, Abla (My University, 2022)
Hepatocellular carcinoma is a condition that occurs almost universally in people with underlying liver disease and is therefore amenable to surveillance. The goal of this research was to determine the different epidemiological, clinical and serological aspects of cirrhosis and cirrhotic liver CHC. The study of our 16 patients was carried out in the University Hospital to Mostaganem in agreement with the Mazagran Oncology Center, taking into account the analysis of biochemical assays and tumor markers in the laboratory and the various clinical abnormalities of the patients through the consultations of specialist doctors and the medical records of each patient, thus studying the morphological aspects of the liver by liver biopsy puncture. The results obtained first revealed a significant prevalence which confirms the severity of hepatic decompensation linked to the presence of hepatic insufficiency including jaundice (50%), hepatic encephalopathy (18.25%) and portal hypertension where the common pathological aspects were ascites (81.25%) and esophageal varices (56.25%). Second, the latter allowed the assessment of liver damage by measuring the degree of severity of cirrhosis by the Child Pugh stage C score (63%) and stage B score (37%), and by performing a PBH as a histological study to determine the size of the nodules and liver masses. Finally, the results revealed a moderate increase in transaminases, gamma GT, alkaline phosphatase, urea, total bilirubin, CRP, platelets and a decrease in TP, albumin and creatinine. Finally, an increase in all tumor markers in cancer patients was observed. It is concluded that portal hypertension and the appearance of ascites fluid are indicative of cirrhosis that can develop in CHC, manifested by the appearance of multiple peritoneal nodules and liver masses.
Keywords: Hepatocellular carcinoma; cirrhosis; portal hypertension; ascites; esophageal varices; transaminases; peritoneal nodules